Pengembangan Komik Digital Tiga Dimensi Untuk Meningkatkan Literasi Sains Dan Sikap Ilmiah Siswa - Mukti, Abdul; Abidin, Zaenal; Arif, Asep Ginanjar (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2023)
This research and development is motivated by the limited use of digital media in the digitalization era applied by teachers in the science learning process so that scientific literacy and students' scientific attitudes are very low and student learning processes become inactive. This research and development aims to describe the products that have been developed by researchers based on the Borg and Gall (1983) model. Data collection was carried out using test, observation, feasibility questionnaires and student response questionnaires. The data analysis used is descriptive quantitative and descriptive Bio Educatio Vol. 7 No. 2 April 2022 | 2 qualitative analysis techniques. The results of the research are as follows: (1) Research and collect information. (2) Planning. (3) Development of initial product forms or research designs. (4) Preliminary field trials on subjects obtained very good categories. (5) The product revision obtained an average score based on the Likert scale, namely from a media expert with a score of 4, a material expert with a score of 4, so that it was categorized as very good and the average score of pedagogic expert 3 was categorized as good. (6) The main field trials of scientific attitude assessment based on indicators of honesty obtained 2.5 with good criteria, curiosity obtained 2.6 with good criteria, openness obtained a value of 2.1 with less criteria and distrust obtained a value of 2.1 with criteria not enough. While on feasibility obtained an average based on media aspects 3.6, language and material aspects 3.6 and benefits aspects 3.5 with good criteria and student responses obtained an average based on media aspects 3.6, language and material aspects 3, 5, the benefit aspect is 3.6 with good criteria. (7) Operational product revision is related to product revision in the fifth stage. (8) Operational field testing obtained values based on the N-gain of the experimental class at pretest 38 and posttest 87 so that there was a significant increase (9) Final product. (10) Mass deployment. Based on the research results, it can be concluded that three-dimensional digital comics can improve scientific literacy and scientific attitude of students so that they are suitable for use in schools.